2009
DOI: 10.1542/peds.2008-0323
|View full text |Cite
|
Sign up to set email alerts
|

Being Bullied: Associated Factors in Children and Adolescents 8 to 18 Years Old in 11 European Countries

Abstract: This study indicated considerable variation between countries in the prevalence of those perceiving themselves to be victims of bullying but also revealed a clear profile of those likely to be bullied. The study also suggests that the Kidscreen bullying scale could be useful in identifying potential bullying victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
141
2
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 33 publications
16
141
2
35
Order By: Relevance
“…School bullying victimisation was associated with a broad range of mental health factors, peer and family relationship difficulties and negative life events in this study, which is consistent with previous research findings ( Analitis et al, 2009, Kaltiala-Heino et al, 1999, Seals and Young, 2003. Both self esteem and serious physical abuse remained in the final explanatory model for boys.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…School bullying victimisation was associated with a broad range of mental health factors, peer and family relationship difficulties and negative life events in this study, which is consistent with previous research findings ( Analitis et al, 2009, Kaltiala-Heino et al, 1999, Seals and Young, 2003. Both self esteem and serious physical abuse remained in the final explanatory model for boys.…”
Section: Discussionsupporting
confidence: 93%
“…As previous studies have reported, we found that boys who had been bullied at school were more anxious and depressed and had poorer self-esteem than those without a history of bullying victimisation (Analitis et al, 2009, Brunstein Klomek et al, 2007, Ivarsson et al, 2005.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Those who are the targets of bullying are classified as victims (Haynie et al 2001;Wolke et al 2000). Bullying is a universal problem, occurring worldwide, with prevalence ranging from approximately 10-25% across countries (Analitis et al 2009;Nansel et al 2001). …”
mentioning
confidence: 99%